Are new EU data market regulations coherent and efficient? - Bertin Martens (Bruegel, 2023)
Technical restrictions on access to and re-use of data may result in failures in data markets and data-driven services markets. Th is paper examines three new EU data regulations (the European Health Data Space, the Data Act and the Digital Markets Act) that vary substantially in mandatory access measures intended to overcome these market failures. It applies three economic criteria, economies of scope in re-use and in aggregation of data, and data supply-side failures, to assess the effi ciency of these regulations in overcoming market failures and coherence across regulations. Variations might be justifi ed by particular sectoral market conditions. Th e European Health Data Space proposal comes close to an ideal data access regime for primary re-use and secondary pooling of health data. Th e Data Act opens access to data from tangible products only. It strengthens the market power of data holders by giving them quasi-ownership rights over data. It introduces new obstacles to re-use that are likely to minimise its impact. Th e Digital Markets Act opens access to market data pools collected by very large gatekeeper platforms. Some access provisions are vaguely defi ned. Others facilitate access to data pools but may risk unwinding the benefi ts of data-driven network eff ects. Th ere is scope for signifi cant improvement in these data regulations.
Keywords: 330